0
$\begingroup$

For the following matrix $$A= \begin{bmatrix} 0 & 1 & 0\\ 1 & 0 & 1\\ 0 & 1 & 1 \end{bmatrix} $$ I need to use the Cayley-Hamilton theorem to calculate $(A+I_3)^{10}(A-I_3)^2+A$

First I try writing the characteristic polynomial $f(t)=\det(A-tI_3)=-t^3+t^2+2t-1$. Then, by using Caylely-Hamilton, I have that $f(A)=O_3$, that is, $$-A^3+A^2+2A-I_3=O_3$$ $$A^3-A^2-2A+I_3=O_3$$ I decompose the previous expression and I get that $$(A+I_3)(A-I_3)^2=A$$ Now I replace the last expression in the initial expression $(A+I_3)^{10}(A-I_3)^2+A$ and get $$(A+I_3)^9(A+I_3)(A-I_3)^2+A=$$ $$=(A+I_3)^9A+A$$

Now what should the next step be?

$\endgroup$
1
$\begingroup$

I am not sure how fruitful your approach will be. One method that will work is as follows: with polynomial long-division, we find that $$ (t + 1)^{10}(t - 1)^2 + t = q(t)(t^3 - t^2 - 2t + 1) + 4631 t^2 + 3721 t - 2560. $$ Thus, we have $$ (A + I)^{10}(A - I)^2 + A = 4631 A^2 + 3721A - 2560 I. $$

$\endgroup$
1
$\begingroup$

You can calculate the last expression as $$(A+I)^9A+A = (((A+I)^3)^2+I)A = \begin{bmatrix} 2070 & 3722 & 4631 \cr 3722 & 6701 & 8353 \cr 4631 & 8353 & 10423 \end{bmatrix}$$ with only $4$ matrix multiplications and $2$ additions with identity $I$ which shouldn't be hard.

$\endgroup$
0
$\begingroup$

Hint: The result is a matrix with integer coeffcients, namely $$ \begin{pmatrix} 2070 & 3722 & 4631 \cr 3722 & 6701 & 8353 \cr 4631 & 8353 & 10423 \end{pmatrix} $$ So you need to evaluate at a certain point.

$\endgroup$
2
  • $\begingroup$ What is that should be evaluated? $\endgroup$ – Miguel Aug 4 '20 at 12:30
  • 1
    $\begingroup$ $(A+I_3)^{10}(A-I_3)^2+A$ should be evaluated. This can be done by replacing $A^3$ repeatedly, ending up with $rA^2+sA+tI$, which you have to compute (evaluate). $\endgroup$ – Dietrich Burde Aug 4 '20 at 12:31
0
$\begingroup$

\begin{align} \det(\lambda I-A)&=\left| \begin{array}{ccc} \lambda & -1 & 0 \\ -1 & \lambda & -1 \\ 0 & -1 & \lambda-1 \end{array} \right| \\ & = \lambda(\lambda(\lambda-1)-1)+((-1)(\lambda-1)) \\ & = \lambda^2(\lambda-1)-(\lambda-1) \\ & =(\lambda-1)^2(\lambda+1). \end{align} Therefore $(A-I)^2(A+I)=0$. You are asked to compute $(A+I)^{10}(A-I)^2+A$, which must be the same as $A$ because $(A+I)^{10}(A-I)^2$ has $(A-I)^2(A+I)$ as a factor.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.